Australia - Brown, G. Mac, 1957-; Knapman, Catherine; Luhrmann, Baz.; Beattie, Stuart; Harwood, Ronald, 1934-; Flanagan, Richard; Kidman, Nicole, 1967-; Jackman, Hugh.; Baroo, Eddie; Brown, Bryan, 1947-; Bazmark Films (Firm); Twentieth Century-Fox Film Corporation (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2009)
In 1940's Australia, an English aristocrat inherits a large ranch. English cattle barons plot to take her land and she reluctantly joins forces with a rough-hewn cattle drover to protect her ranch. Together they experience four life-altering years, a love affair and the bombing of Darwin during World War II.
Widescreen.
Title from container.
Originally released as a motion picture in 2008.
Special features: Deleted scenes.
Director of photography, Mandy Walker ; editors, Dody Dorn, Michael McKucker ; music, David Hirschfelder.
Nicole Kidman, Hugh Jackman, Eddie Baroo, Bryan Brown.
Keywords: Aristocracy (Social class) -- Australia -- Drama; Cattle breeders -- Australia -- Drama; Drovers -- Australia -- Drama; Ranches -- Australia -- Drama; World War, 1939-1945 -- Aerial operations -- Drama; Action and adventure films; Feature films; Films for the hearing impaired; Action and adventure films; War films; Western films